2014
DOI: 10.1111/avsc.12102
|View full text |Cite
|
Sign up to set email alerts
|

Burning season does not affect post‐fire regeneration but fire alters the balance of the dominant species in a seeder‐dominated Mediterranean shrubland

Abstract: Question: In a seeder-dominated shrubland, does burning season affect postfire regeneration? Are herbs and shrubs similarly affected? Is the dominance of the main species modified by burning and its timing?Location: Los Puntales, Sierra Morena (C ordoba, southern Spain). Methods:The shrubland was 12 yr old, dominated by several species of Cistus, among the main seeders. Four blocks, each containing plots of 25 9 25 m, were burned in late May (early season, ES) and late September (late season, LS) with similar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
12
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 42 publications
4
12
0
1
Order By: Relevance
“…Our results on C. rubrifolium constitute a step towards explaining the physiology of the well-known post-fire establishment behaviour of annual plants in the Mediterranean Basin. Indeed, the stimulation of germination with several fire-related cues in our laboratory experiments is in accordance with the field observations on the seedling emergence of C. rubrifolium in the first year after a fire (Céspedes et al, 2014;G. Ergan et al, Hacettepe University, Ankara, Turkey, unpublished observations).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results on C. rubrifolium constitute a step towards explaining the physiology of the well-known post-fire establishment behaviour of annual plants in the Mediterranean Basin. Indeed, the stimulation of germination with several fire-related cues in our laboratory experiments is in accordance with the field observations on the seedling emergence of C. rubrifolium in the first year after a fire (Céspedes et al, 2014;G. Ergan et al, Hacettepe University, Ankara, Turkey, unpublished observations).…”
Section: Discussionsupporting
confidence: 91%
“…1A). Although there were a few observations of the post-fire emergence of C. rubrifolium (Céspedes et al, 2014;G. Ergan et al, Hacettepe University, Ankara, Turkey, unpublished observations), nothing is known about the mechanism of population regeneration by germination following fire.…”
Section: Speciesmentioning
confidence: 99%
“…A similar result was reported in a previous study, in the western Mediterranean Basin, examining the effect of fire season on germination density from the soil seed bank (Céspedes et al., ). A vegetation survey in this same experimental system revealed no significant differences in the abundances of resprouters and seeders between burning seasons (Céspedes, Torres, Perez, Luna, & Moreno, ). Other studies asserted that germination of obligate seeders is affected by time between the physical dormancy break of seeds by fire heat and the onset of the rainy season (Daskalakou & Thanos, ; Ooi, Auld, & Whelan, ; Pausas, Ribeiro, & Vallejo, ; Prevosto, Gavinet, Ripert, & Fernandez, ).…”
Section: Discussionmentioning
confidence: 78%
“…Our research indicated that seeds of this species have a high-level of dormancy, and they germinate only when some fire-related germination cues are applied (Tavşanoğlu et al 2017). This germination behaviour of this annual species can explain why it is scarce, and can be found in recently burned Mediterranean sites (Céspedes et al 2014, Tavşanoğlu et al 2017. Fernandes (1971) defined three subspecies and two forms for European C. rubrifolium, and following his treatment, Sutton (1988) divided the species into four subspecies: subsp.…”
Section: Resultsmentioning
confidence: 97%